2011
DOI: 10.1093/infdis/jir084
|View full text |Cite
|
Sign up to set email alerts
|

Fully Human Monoclonal Antibody Directed to Proteolytic Cleavage Site in Severe Acute Respiratory Syndrome (SARS) Coronavirus S Protein Neutralizes the Virus in a Rhesus Macaque SARS Model

Abstract: This study represents a platform to produce fully human antibodies against emerging infectious diseases in a timely and safe manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…We further demonstrated that the neutralizing activity induced by the SP3 peptide was specific for the postbinding and membrane fusion steps of MERS infection. Our data are consistent with a previous report on SARS-CoV (17), which indicated that human monoclonal antibody (5H10) directed to proteolytic cleavage site (791-805 amino acid) in S neutralized the virus in a rhesus macaque SARS model. Since multiple neutralizing epitopes have been identified on the S protein of SARS-CoV and envelope of HIV-1 (3,10,13,17), it is not unusual to find more than one neutralizing epitope on the MERS-CoV S protein.…”
Section: Discussionsupporting
confidence: 93%
“…We further demonstrated that the neutralizing activity induced by the SP3 peptide was specific for the postbinding and membrane fusion steps of MERS infection. Our data are consistent with a previous report on SARS-CoV (17), which indicated that human monoclonal antibody (5H10) directed to proteolytic cleavage site (791-805 amino acid) in S neutralized the virus in a rhesus macaque SARS model. Since multiple neutralizing epitopes have been identified on the S protein of SARS-CoV and envelope of HIV-1 (3,10,13,17), it is not unusual to find more than one neutralizing epitope on the MERS-CoV S protein.…”
Section: Discussionsupporting
confidence: 93%
“…Antibodies against RBD and S2 domain of SARS-CoV and MERS-CoV S proteins have been found effective in neutralizing infections of permissive cell lines in vitro [52][53][54][55]. In addition, neutralizing antibodies were capable of treating infections in experimental animals and in infected patients during these major outbreaks [56][57][58][59]. In one study, several SARS-CoV RBD-specific monoclonal antibodies did not bind to SARS-CoV-2 S protein [43].…”
Section: Of 15mentioning
confidence: 99%
“…ACE2 as a receptor for viral entry [3,10], several SARS-CoV RBD-directed mAbs did 2 0 6 not cross-react with SARS-CoV-2 RBD [27,28]. To CoV [29][30][31]. To CoV [29][30][31].…”
Section: Mab1a9 Binds To S Expressed In Sars-cov-2-infected Cellsmentioning
confidence: 99%